Analisa Kemampuan Meredam Suara Pada Batu Bata Komposit Berbahan Dasar Semen, Pasir, Faba (Fly Ash Bottom Ash) - Kosar, Riko Wahyuddin; Hasbi, Muhammad; Aminur, Aminur (Teknik Mesin Universitas Halu Oleo, 2018)
Noise is one of urban people everyday life challenge as many world societies have to encounter. Thus noise reduction material is highly required.This research aims to contain the suitable mixture of composite brick made of faba, cement, and sand for noise reduction furthermore this research also aim to understand and analyze composite brick made of faba (fly ash and bottom ash)in noise reduction towards frequency of 1200 Hz, 1300 Hz, 1400 Hz, 1500 Hz and 1600 Hz. This experiment developed through three variants of different composition which used faba, cement, and sand material. The experiment result exhibit that in the material of volume fraction 10:30:60% on specimen 1 obtained the highest coefficient value of absorptive sound 0.34104 dB with frequency of 1600 Hz and the lowest coefficient value of absorptive sound 0.14721 dB in volume fraction 20:30:50% with frequency of 1200 Hz, on specimen 5. The higher of absorptive sound coefficient value impacted to the more excellent quality of noise reduction material. Keywords: Cement, sand, faba, noise absorption coefficient.